Journals and repositories: an evolving relationship? - Pinfield, Stephen (ALPSP, 2009)
It is now widely accepted that there are two routes to open access (OA): OA repositories and OA journals. It is often assumed these are distinct alternative parallel tracks. However, it has recently become clear that there is potential for repositories and journals to interact with each other on an ongoing basis and between them to form a coherent OA scholarly communication system. This paper puts forward three possible models of interaction between repositories and journals; services such as arXiv and PubMed Central, and the work carried out by the RIOJA project, are working exemplars and pilot implementations of these models. The key issues associated with the widespread adoption of these models include repository infrastructure development; changing ideas of the ‘journal’, ‘article’, and ‘publication’; version management; quality assurance; business and funding models; developing value-added features; content preservation; policy frameworks; and changing roles and cultures within the research community.